2012
DOI: 10.1002/eco.1304
|View full text |Cite
|
Sign up to set email alerts
|

Non rainfall moisture interception by dwarf succulents and their relative abundance in an inland arid South African ecosystem

Abstract: Dwarf succulents persist in the arid Succulent Karoo despite the low‐water storage capacities of their contracted leaves and stems that are inadequate for enduring severe and prolonged drought. We examined the contribution of non‐rainfall moisture (fog, dew, water vapour) to the water budgets and relative abundance of two endemic dwarf succulents Agyroderma pearsonii and Cephalophyllum spissum. Non‐rainfall moisture was measured with automated lysimeters containing bare quartz‐gravel soils and introduced A. pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 68 publications
0
29
0
Order By: Relevance
“…Plant canopies are ideal dew and fog interceptors (Vogel and Müller-Doblies, 2011) and the excess of water harvested over the canopystorage capacity is transferred to the soil surface via stem flow or leaf drip where it is absorbed by the plant root system (Hutley et al, 1997). Also the adsorption of atmospheric water vapour by soils and its uptake by the superficial roots of plants are vital in sustaining their growth and survival and in determining their distributions and relative abundance in arid zones (Matimati et al, 2013). Similarly, our results point out a significant water supply by NRWI on plants, providing water on their surface and in the soil underneath.…”
Section: Discussionmentioning
confidence: 99%
“…Plant canopies are ideal dew and fog interceptors (Vogel and Müller-Doblies, 2011) and the excess of water harvested over the canopystorage capacity is transferred to the soil surface via stem flow or leaf drip where it is absorbed by the plant root system (Hutley et al, 1997). Also the adsorption of atmospheric water vapour by soils and its uptake by the superficial roots of plants are vital in sustaining their growth and survival and in determining their distributions and relative abundance in arid zones (Matimati et al, 2013). Similarly, our results point out a significant water supply by NRWI on plants, providing water on their surface and in the soil underneath.…”
Section: Discussionmentioning
confidence: 99%
“…11). Overall, both genera of dwarf succulent show a significant loss in habitat and are negatively affected by the future climate changes especially as they rely heavily on non-rainfall moisture events such as fog, dew and water vapour [6]. The ability of these genera to migrate across the landscape and occupy newly suitable areas identified in this study is thought to be extremely limited, especially considering the timescale involved.…”
Section: Projected Future Changes and Discussionmentioning
confidence: 88%
“…Previous studies have shown that the current distribution of Conophytum and Lithops is less dependent on rainfall and temperature, but instead relies more on non-rainfall moisture such as fog, dew, and water vapour [2,6]. Due to the general lack of other forms of non-rainfall data, in this study we used fog data, with the additional variable of relative humidity as climate variables.…”
Section: Climate Data and Methodologymentioning
confidence: 99%
“…Fog is recognised to be especially prevalent on the west coast and along some larger river systems, notably the Orange River. The contribution made by dew to annual precipitation appears to be less pronounced (<20-fold less), although it is much more widespread than the effects of fog (Matimati et al, 2013).…”
Section: Introductionmentioning
confidence: 87%
“…Rainfall declines east to west and south to north but is also characterised by its unpredictable nature. Non-rainfall moisture is thought to make a significant contribution to make a substantial, and reliable, contribution to total moisture availability (Matimati et al, 2013). Fog is recognised to be especially prevalent on the west coast and along some larger river systems, notably the Orange River.…”
Section: Introductionmentioning
confidence: 99%